Exploring Concepts of Contagion and the Authority of Medical Treatises in 14th-16th Century England - Jones, Lori K (Université d'Ottawa / University of Ottawa, 2012)
This thesis examines whether and how historians’ reliance on medical treatises has limited the historiography of contagion as it relates to fourteenth through sixteenth century England. It analyses the context, contents, audience, and codicology of six English tractates, four on the plague and two on the sweating sickness. Before the early seventeenth century, most English tractates were translations/adaptations of Continental works, with ‘uniquely English’ content added. Although the plague dominates studies of pre-modern disease, focusing on the plague hinders comparative analyses that can reveal much about contemporary understanding of contagion. The socio-political-professional contexts in which the tractates were written and disseminated affected their contents, circulation and, ultimately, audiences. Although largely ignored by historians, the tractates’ prefatory dedications, together with their codicology, reveals that the texts were likely accessible to non-elite audiences. Rather than being limited to its medical sense, contagion formed part of the larger discourse about the human condition.
Keywords: plague tractates; plague; sweating sickness; England; late medieval; early modern; contagion; contagious disease; history of medicine; medical treatises; literacy/reading; codicology; John Caius; Thomas le Forestier; Thomas Moulton; Thomas Phayer; Canutus; BL Additional MS 27582; BL Sloane MS 3489; professional conflict; socio-political conflict; fifteenth century; sixteenth century